CRIMINAL LIABILITY FOR CULTIVATION OF PLANTS PROHIBITED IN THE REPUBLIC OF UZBEKISTAN (American Journal of Pedagogical and Educational Research, 2023)
In this article, the crops that are prohibited to be grown in the Republic of Uzbekistan, on what basis they are prohibited, and the criminal punishments established for this act were studied. Also, some theoretical and practical problems related to the qualification of the crime of cultivation of prohibited crops were highlighted, and in this regard, relevant proposals and recommendations were developed for improving the criminal legislation of the Republic of Uzbekistan.